Fetal Hyperthyroidism Secondary to Maternal Basedow–Graves' Disease - Soto, Julio; Weissglas, Bunio; von Plessing-Pierry, Gustav; del Solar, Maria Paz; Peña-Villa, Carolina; Flores, Ximena; Arancibia, Monica; Campos, Laura (American Journal of Perinatology Reports, 2024)
Fetal hyperthyroidism is a rare prenatal disease and can be life-threatening. The diagnosis is based on ultrasound in mothers with a history of Basedow–Graves' disease and elevation of thyrotropin receptor antibodies (TRAbs) levels. The treatment consists of antithyroid drugs. We present a mother with Basedow–Graves' disease, treated with radioactive iodine 16 years ago. She had an unplanned pregnancy at the age of 29 years, and an elevation of TRAbs (21 U/L) was found at the sixth week of pregnancy. At 22 weeks of gestation, fetal ultrasound displayed tachycardia, goiter, exophthalmos, and suspicion of craniosynostosis, hence methimazole was started. Concomitantly, suppressed maternal thyroid-stimulating hormone (TSH) was found. Her daughter was born at 33 + 6 weeks showing clinical and laboratory findings of hyperthyroidism. Consequently, treatment with methimazole was prescribed. Normal thyroid function was documented in the mother after giving birth. Clear explanation has not been found for the alteration of maternal TSH during pregnancy.
Keywords: fetal hyperthyroidism; Graves' disease; hyperthyroidism; fetal